A bizarre parosteal osteochondromatous proliferation at the sesamoid bone of the hallux: A case report. (18th February 2019) - Takeda, Shinsuke; Nishimura, Akinobu; Nakazora, Shigeto; Sudo, Akihiro; Hirata, Hitoshi; Kato, Ko
A bizarre parosteal osteochondromatous proliferation (BPOP) is a rare, benign, osseous tumor that presents as an exophytic cortical growth consisting of bone, cartilage, and fibrous tissue. However, the identification of BPOP by preoperative imaging along with appropriate diagnosis and treatment without recurrence is challenging, particularly for BPOPs that rarely develop in certain parts of the body. Herein, we report a rare case involving a BPOP at the sesamoid bone of the hallux that was first suspected on preoperative computed tomography imaging. There has been no recurrence 3 years after surgical resection.